5 The art of compromise: co-production of evidence in applied health research. Issue Volume 23:Issue Supplement 1(2018) (June 2018) - Kislov, Roman; Wilson, Paul; Knowles, Sarah; Boaden, Ruth
Abstract : Objectives: Co-production approaches, variously referred to as integrated knowledge translation, participatory research and co-design, provide an alternative to the traditional 'push' and 'pull' modes of translating research evidence into better healthcare. Despite the growing importance of the impact agenda and the proliferation of collaborative research partnerships, awareness about the practical realities of co-production remains low. This interactive workshop, drawing on the ongoing programme of research conducted by the workshop organisers as well as on their personal experiences, will address the following learning objectives: To explore different definitions and types of co–production in applied health research. To examine tensions and compromises involved in co–production. To discuss the implications of the co-production for the focus and outputs of research as well as for the structure and function of the research team. To analyse the factors influencing the processes and outcomes of co-production. To share personal experiences of co-production. Method: The workshop will be delivered by an experienced team comprised of the Director of a large-scale co-production programme, an editor of Implementation Science and two researchers involved in studying co-production as part of the NIHR CLAHRC-funded research project. By combining experiential and empirical evidence, the workshop will provide both practical tips about how to make co-production work and a more critical exploration of its limitations and unintended consequences. The time will be split equally between the didactic component, summarising the existing research on co-production, and the interactive component, where workshop participants will work together in small groups, reflecting on the information presented and sharing their own experiences. We will facilitate a participatory group exercise, which will produce an outline of key practical steps involved in co-designing applied health research proposals with practitioners and/or service users. Microsoft PowerPoint sides, flip charts and post-it notes will be used during the workshop. Results: We aim to show that although co-production approaches may differ depending on the stage(s) of the research process in which they are deployed as well as on the type of stakeholders involved, all of them require a number of compromises directly affecting the collaborators. Contrasting the expectations of healthcare practitioners with the researchers' way(s) of doing things, we categorise these compromises into three broad groups: (1) complementing 'research' by 'non-research activities', such as implementation, improvement and education; (2) opening up the research team to include project managers, practitioners, and service users as well as to bring together researchers espousing different epistemological and methodological paradigms; and (3) adapting to a practice-driven agenda and embracing impact as an essential component of evaluation and research. We will also discuss the 'dark side' of co-production, alerting the workshops participants to its potential limitations, and suggest possible ways to address these in practice. Conclusions: By uncovering the tensions and complexities involved in co-production of evidence, our workshop will touch upon a number of broader topical issues currently facing the community of researchers involved in evidence-based healthcare. How to strike the balance between the production of high-quality evidence and its implementation in actual practice? Does participation in practice-driven research projects represent a 'career suicide' for early-career researchers or an opportunity to develop a unique and exciting career trajectory? How to foster the cadre of implementation-savvy researchers and research-savvy practitioners? This interactive workshop will aim to represent multiple perspectives and facilitate constructive dialogue between them.